The Role of the TGF-β Coreceptor Endoglin in Cancer - Eduardo Pérez-Gómez; Gaelle del Castillo; Juan Francisco Santibáñez; Jose Miguel Lêpez-Novoa; Carmelo Bernabéu; Miguel Quintanilla (The Scientific World Journal)
Endoglin (CD105) is an auxiliary membrane receptor of transforming growth factor beta (TGF-β) that interacts with type I and type II TGF-β receptors and modulates TGF-β signaling. Endoglin is overexpressed in the tumor-associated vascular endothelium, where it modulates angiogenesis. This feature makes endoglin a promising target for antiangiogenic cancer therapy. In addition, recent studies on human and experimental models of carcinogenesis point to an important tumor cell–autonomous role of endoglin by regulating proliferation, migration, invasion, and metastasis. These studies suggest that endoglin behaves as a suppressor of malignancy in experimental and human epithelial carcinogenesis, although it can also promote metastasis in other types of cancer. In this review, we evaluate the implication of endoglin in tumor development underlying studies developed in our laboratories in recent years.